b=(11b+14)(8-10b)

Simple and best practice solution for b=(11b+14)(8-10b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b=(11b+14)(8-10b) equation:


Simplifying
b = (11b + 14)(8 + -10b)

Reorder the terms:
b = (14 + 11b)(8 + -10b)

Multiply (14 + 11b) * (8 + -10b)
b = (14(8 + -10b) + 11b * (8 + -10b))
b = ((8 * 14 + -10b * 14) + 11b * (8 + -10b))
b = ((112 + -140b) + 11b * (8 + -10b))
b = (112 + -140b + (8 * 11b + -10b * 11b))
b = (112 + -140b + (88b + -110b2))

Combine like terms: -140b + 88b = -52b
b = (112 + -52b + -110b2)

Solving
b = 112 + -52b + -110b2

Solving for variable 'b'.

Reorder the terms:
-112 + b + 52b + 110b2 = 112 + -52b + -110b2 + -112 + 52b + 110b2

Combine like terms: b + 52b = 53b
-112 + 53b + 110b2 = 112 + -52b + -110b2 + -112 + 52b + 110b2

Reorder the terms:
-112 + 53b + 110b2 = 112 + -112 + -52b + 52b + -110b2 + 110b2

Combine like terms: 112 + -112 = 0
-112 + 53b + 110b2 = 0 + -52b + 52b + -110b2 + 110b2
-112 + 53b + 110b2 = -52b + 52b + -110b2 + 110b2

Combine like terms: -52b + 52b = 0
-112 + 53b + 110b2 = 0 + -110b2 + 110b2
-112 + 53b + 110b2 = -110b2 + 110b2

Combine like terms: -110b2 + 110b2 = 0
-112 + 53b + 110b2 = 0

Begin completing the square.  Divide all terms by
110 the coefficient of the squared term: 

Divide each side by '110'.
-1.018181818 + 0.4818181818b + b2 = 0

Move the constant term to the right:

Add '1.018181818' to each side of the equation.
-1.018181818 + 0.4818181818b + 1.018181818 + b2 = 0 + 1.018181818

Reorder the terms:
-1.018181818 + 1.018181818 + 0.4818181818b + b2 = 0 + 1.018181818

Combine like terms: -1.018181818 + 1.018181818 = 0.000000000
0.000000000 + 0.4818181818b + b2 = 0 + 1.018181818
0.4818181818b + b2 = 0 + 1.018181818

Combine like terms: 0 + 1.018181818 = 1.018181818
0.4818181818b + b2 = 1.018181818

The b term is 0.4818181818b.  Take half its coefficient (0.2409090909).
Square it (0.05803719008) and add it to both sides.

Add '0.05803719008' to each side of the equation.
0.4818181818b + 0.05803719008 + b2 = 1.018181818 + 0.05803719008

Reorder the terms:
0.05803719008 + 0.4818181818b + b2 = 1.018181818 + 0.05803719008

Combine like terms: 1.018181818 + 0.05803719008 = 1.07621900808
0.05803719008 + 0.4818181818b + b2 = 1.07621900808

Factor a perfect square on the left side:
(b + 0.2409090909)(b + 0.2409090909) = 1.07621900808

Calculate the square root of the right side: 1.037409759

Break this problem into two subproblems by setting 
(b + 0.2409090909) equal to 1.037409759 and -1.037409759.

Subproblem 1

b + 0.2409090909 = 1.037409759 Simplifying b + 0.2409090909 = 1.037409759 Reorder the terms: 0.2409090909 + b = 1.037409759 Solving 0.2409090909 + b = 1.037409759 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-0.2409090909' to each side of the equation. 0.2409090909 + -0.2409090909 + b = 1.037409759 + -0.2409090909 Combine like terms: 0.2409090909 + -0.2409090909 = 0.0000000000 0.0000000000 + b = 1.037409759 + -0.2409090909 b = 1.037409759 + -0.2409090909 Combine like terms: 1.037409759 + -0.2409090909 = 0.7965006681 b = 0.7965006681 Simplifying b = 0.7965006681

Subproblem 2

b + 0.2409090909 = -1.037409759 Simplifying b + 0.2409090909 = -1.037409759 Reorder the terms: 0.2409090909 + b = -1.037409759 Solving 0.2409090909 + b = -1.037409759 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-0.2409090909' to each side of the equation. 0.2409090909 + -0.2409090909 + b = -1.037409759 + -0.2409090909 Combine like terms: 0.2409090909 + -0.2409090909 = 0.0000000000 0.0000000000 + b = -1.037409759 + -0.2409090909 b = -1.037409759 + -0.2409090909 Combine like terms: -1.037409759 + -0.2409090909 = -1.2783188499 b = -1.2783188499 Simplifying b = -1.2783188499

Solution

The solution to the problem is based on the solutions from the subproblems. b = {0.7965006681, -1.2783188499}

See similar equations:

| 5x+8=3(x+4) | | b=8a(8A-13) | | 8p+p^2=105 | | 8x+19=2x+163 | | b=-(-5a-3)+(-5+8a) | | -3p+2q-3r= | | 3x-7=2x+18 | | 253-3x=42x+23 | | 11a+6b+24ao+18b= | | 125=5x^3 | | 4x^3+9x^2-2=0 | | (h*h)+h=6 | | 4Y-3=29 | | 2(h*h)+h=21 | | 6(h*h)+2h=28 | | 0=x^2-78x-1911 | | 2Y=128 | | Y-7=21 | | 5y+11=3(y+7) | | X+16=35 | | 7x+5=(2x+3)(4x+1) | | 2x^2+14x+54=0 | | x^2+14+54=0 | | 7x-x^2-15=0 | | 10(3k+1)=2(9+11) | | x+(x+1)=10 | | -x^2-2x+4=0 | | 4(x+2)-2=34 | | 107-6x=21x+23 | | 2n^2+n=0 | | 9(q-2)=3(9-12) | | 10-8x=125-43x |

Equations solver categories